Persepsi Guru Tentang Kepemimpinan Kepala Sekolah DanFasilitas Mengajar Guru Terhadap Kinerja Guru Di SMK Muhammadiyah 1 Sambi Boyolali - Prayogo, Ridwan, Drs. Muhammad Yahya, M.Si (2017)
This res earch aims to know: 1) Influence of headmaster leadership on teacher performance, 2) Influence of teacher teaching facility to teacher performance, 3) influence of principal leadership and teacher teaching facility to teacher performance. This type of research includes quantitative descriptive research with the conclusion through statistical methods. The study included population research with 32 respondents. The instruments used in this study are questionnaires and documentation. Questionnaire previously tested and validity and reliability test. Data analysis techniques used are multiple linear regression analysis, t test, F test, determination coefficient (R2), predictor contribution (SR and SE). Regression analysis results obtained by regression equation; Y = 32.192 + 1.077X1 + 0,533X2. The equation shows that teacher performance is influenced by the principal's leadership and teacher's teaching facilities. The conclusion that can be drawn is; 1) The leadership of the principal has a positive effect on teacher performance. This is based on regression analysis (t test) known that tcount> ttable is 3,142> 2,045 with significance value <0,05 and effective contribution (SE) equal to 35,8% and relative contribution (SR) equal to 60,5%. 2) Teacher teaching facilities have a positive effect on teacher performance. This is based on regression analysis (t test) tcount> ttable that is 2,202> 2,045 with significance value 0,05 and effective contribution (SE) equal to 23,3% and relative contribution (SR) equal to 39,5%. Principal leadership and teacher teaching facilities on teacher performance. This is based on analysis of multiple linear regression variation (F test) known that Fcount> Ftable is 20,945> 3,328 with significance value 0,05 and coefficient of determination (R2) equal to 59,1% indicate that the influence of principal leadership and teacher teaching facility to performance Teachers accounted for 59.1%. While the rest influenced by other variables.